Optimization of Kefir Tablet Formulation using Acacia Gum as A Natural Binding Agent - Hestiary Ratih; Ridha Dwita Putri; Slamet Ibrahim; Mira Andam Dewi (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Kefir enriched with Lactic Acid Bacteria (LAB) potentially has excellent health benefits as a probiotic beverage but its stability in liquid forms is limited. In order to attain stabilization and standardization of appropriate doses, kefir was converted to powders and subsequently formed into tablets using the wet granulation method after spray drying. This study aimed to optimize the formulation by comparing three concentrations of gum acacia (F1: 5%, F2: 10%, F3: 15%) as a natural binder and protective agent. Granule evaluation confirmed all formulations had low moisture content and good flow properties, with F3 exhibiting the best compressibility index (12.78%). Tablet evaluation showed all formulations met the friability (≤ 1%) and disintegration time (≤ 15 minutes) requirements. For tablet hardness, only F2 and F3 met the specification (≥ 4 kP), with F3 achieving the highest value (6.12 ± 0.09 kP). LAB viability showed a positive correlation with binder concentration, with F3 producing the highest colony count (709 ± 1.4 x 107 CFU/g). Throughout, F3 was able to produce the best quality intact matrices, extensive protective matrices, and outstanding viability among the LAB, F3 has pronounced to be the most propitious to be a very stable probiotic nutraceutical formulation.